Pengaruh Program Bimbel Reading Terhadap Kemampuan Membaca Anak kelas 1 di SD Negeri 130/IV Kota Jambi - Mariatul Kubro Khoiri naya; Ani Rizki; Uswatul Hasni (GLOBAL SCIENTS PUBLISHER, 2025)
This program aims to improve the reading skills of first-grade students at SD Negeri 130/IV in Jambi City through a reading tutoring program. The main issue underlying this research is the low reading ability of students, which was observed during initial classroom observations. Ten students struggled to recognize and differentiate simple letters and had difficulties in spelling. To address this issue, the researcher implemented a reading tutoring program specifically designed to help studentsdistinguish between alphabet letters and spell fluently. The method used in this reading tutoring program is a step-by-step learning approach, where students are given the opportunity to learn reading in turns, under the direct supervision of the instructor. The research results showed positive outcomes, as all students participating in the reading tutoring program demonstrated significant improvement in their ability to recognize letters and read. An evaluation was conducted after 5 weeks, and the results indicated that students who previously struggled to differentiate alphabet letters and spell could now read well. This reading tutoring program not only benefits the enhancement of students' reading skills but also strengthens the collaboration between parents and the school. It is hoped that similar programs can continue to be implemented to maintain students' reading fluency in the future.